LOW ENGLISH PROFICIENCY STUDENTS' ANXIETY AND THE PROGRESS OF THEIR ORAL PROFICIENCY WHEN INTERACTING WITH A NATIVE SPEAKER - Imelda Wahyuni Husein, - (2019)
Students in Indonesia mostly experience difficulty and high anxiety in speaking English because of the lack of vocabulary, fluency, accuracy, confidence, and also exposure. This study entitled "Low English proficiency Students' Anxiety and the Progress of their Oral Proficiency when Interacting with a Native Speaker" is aiming to investigate how low proficiency students interact with a native speaker of English and how they develop their speaking skill and also handle their anxiety. This study used qualitative research involving four 10th grade students in one Vocational High School in Bandung region, Indonesia. The sample was taken purposively in order to get the uniqueness. The data were collected based on observation, interview, and questionnaire results. Observations were conducted in this study to investigate four low English proficiency students' interaction with a native speaker of English during 10 meetings. An interview was also conducted to find out what students feel when they have a conversation with a native English-speaking teacher, progress in their speaking skill, and how they handle their anxiety. Questionnaires were also distributed to compare low and high proficiency students' feeling and thought. According to the observation findings, low proficiency students experienced an improvement in their oral proficiency after interacting with a native speaker even if they faced several difficulties. The interview and questionnaire results show that they are more confident and motivated in speaking English after having a conversation with a native speaker. Therefore, it is suggested that if it is necessary, the teachers make a collaboration or work together with native speakers in order to improve students' oral proficiency.